140k views
0 votes
Factorise x squared + 4x + 3 ​

User Jaynabonne
by
4.8k points

1 Answer

4 votes

Answer: (x+1)(x+3)

===================================================

Step-by-step explanation:

Let's assume it factors into (x+a)(x+b)

The goal is to find the two numbers a and b.

FOIL out (x+a)(x+b) to get x^2+(a+b)x+ab

Note how a+b is the middle term and ab is the last term.

In the original expression, 4 is the middle term and 3 is the last term.

So we need to find two numbers that

  • add to 4
  • multiply to 3

There are two ways to multiply to 3 and they are

  • 1 times 3 = 3
  • -1 times -3 = -3

But only the first way has the factors add to 4. So that means a = 1 and b = 3.

Therefore (x+a)(x+b) = (x+1)(x+3)

And x^2+4x+3 = (x+1)(x+3)

User Arvind Bhardwaj
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.